Lean implementation: organizations approach to excellence - Khalili, Amjad; Ismail, Md Yusof; Che Daud, Mohd Radzi (Noor Publishing, 2018)
This new book about lean paradigm is a virtuous guide and reference for scholars, practitioners, researchers, leaders and managers who need to understand, recognize and practice lean in professional manner. It implies responsiveness, case studies, lean terminologies and enriches the lean culture inside enterprises towards being successful. In more details, it performed as an umbrella for the numerous lean tools, techniques, principles, practices and common factors which if correctly managed and directed by enterprises will assist these to be an innovative and sustain operations on the long term mechanism. Referring to managers‘ continuous efforts to direct operations, staff and activities to enhance knowledge towards adopting lean philosophy, this book also introduces ideal models which could be considered as portfolio to help enterprises become world class in this competitive world and manage operations successfully